Application of natural polysaccharides and their novel dosage forms in gynecological cancers: therapeutic implications from the diversity potential of natural compounds - Li, Yi; Zhang, Chuanlong; Feng, Lu; Shen, Qian; Liu, Fudong; Jiang, Xiaochen; Pang, Bo (Frontiers in Pharmacology, 2023)
Cancer is one of the most lethal diseases. Globally, the number of cancers is nearly 10 million per year. Gynecological cancers (for instance, ovarian, cervical, and endometrial), relying on hidden diseases, misdiagnoses, and high recurrence rates, have seriously affected women’s health. Traditional chemotherapy, hormone therapy, targeted therapy, and immunotherapy effectively improve the prognosis of gynecological cancer patients. However, with the emergence of adverse reactions and drug resistance, leading to the occurrence of complications and poor compliance of patients, we have to focus on the new treatment direction of gynecological cancers. Because of the potential effects of natural drugs in regulating immune function, protecting against oxidative damage, and improving the energy metabolism of the body, natural compounds represented by polysaccharides have also attracted extensive attention in recent years. More and more studies have shown that polysaccharides are effective in the treatment of various tumors and in reducing the burden of metastasis. In this review, we focus on the positive role of natural polysaccharides in the treatment of gynecologic cancer, the molecular mechanisms, and the available evidence, and discuss the potential use of new dosage forms derived from polysaccharides in gynecologic cancer. This study covers the most comprehensive discussion on applying natural polysaccharides and their novel preparations in gynecological cancers. By providing complete and valuable sources of information, we hope to promote more effective treatment solutions for clinical diagnosis and treatment of gynecological cancers.